Favouring Middle-and Upper-Class Students? The Structure and Process of Attending China’s Selective Universities - Ailei, Xie; Kuang, Huan; Hong, Yanbi (Central European Journal of Educational Research, 2023)
Research suggests the increasing influence of family socioeconomic status, as measured by parents’ income and occupations, in access to Chinese higher education. Yet, the literature remains inconclusive about the extent to which the social background of rural and urban students is associated with academic and social performance at elite universities. We address this limitation by looking at the academic and social success of representative samples of first- and second-year students enrolled at four Chinese elite universities. Our aim is to understand the characteristics that students from both urban and rural environments bring with them and how those characteristics bear on academic and social performance in university. We found an overrepresentation of students from middle- and upper-class backgrounds in both urban and rural student groups. The fact that the process indicator of cultural capital has a direct association with social success suggests students from urban areas exhibit traits valued in the selective university environment.